Great house [book club bag] - Krauss, Nicole (W. W. Norton & Co., 2010)
Connected solely by a desk of enormous dimension and many drawers that exerts a power over those who possess it or give it away, three people--a lonely American novelist clinging to the memory of a poet who has mysteriously vanished in Chile, an old man in Israel facing the imminent death of his wife of 51 years, and an esteemed antiques dealer tracking down the things stolen from his father by the Nazis--struggle to create a meaningful permanence in the face of inevitable loss.